The Role of Virtual Education Networks on Students' Mental Health - Oday Khalid Lazim AL- Tameemi; Mohammad Ali Nadi; Zahra Yazdani; Raed Rasim Younus Aljbara (Shiraz University of Medical Sciences, 2024)
Background: The Covid-19 pandemic changed the world; its most important achievement for education was changing the approach from traditional to virtual education. The present study aimed to investigate the role of virtual education networks on mental health of students including personality, beliefs, scientific, and cultural dimensions, in selected countries.Methods: This was an exploratory and applied study. According to the phenomenology strategy, theoretical saturation occurred after 24 semi-structured and targeted qualitative interviews with teachers from Iran, Iraq, Syria and Lebanon, in 2023. Quantitative data was collected through a researcher-made online questionnaire with 423 participants. Teachers with at least a Bachelor's degree and five years of teaching experience were selected as the study participants. PLS software version 3 was used to analyze the quantitative data.Results: After analyzing the qualitative interviews, 131 open codes were extracted, and grouped into 22 components and 4 concepts. The results of the quantitative data analysis (factor load) showed the effect of virtual education networks on personality (0.590), beliefs (0.819), scientific (0.564), and cultural (0.815) dimensions which indicate a statistically significant effect. Accordingly, students' belief is mostly affected by virtual education networks. The subcomponents of duality and moral-social confusion in the belief dimension, changing life and nutrition patterns in the cultural dimension, increasing communication and interpersonal problems in the personality dimension, and boredom and frustration in the scientific dimension were highly effective.Conclusions: The study results showed that virtual education acts like a double-edged sword, with both negative and positive effects on the body and mind of students, which necessitates more careful monitoring.